The Absence of the ‘Surrogacy Contract’ from Judicial Constructions of Surrogacy - Brown, Alan (feminists@law, 2018)
This paper explores the absence of the ‘surrogacy contract’ from recent judicial decisions on surrogacy. In The Sexual Contract Pateman argued that, ‘[o]nly masculine beings are endowed with the attributes and capacities necessary to enter into contracts’ and therefore that the sexual contract was ignored in the establishment of patriarchal norms. The central principles of the regulation of surrogacy in the UK are set out in the Surrogacy Arrangements Act 1985; s.1A states that surrogacy arrangements are unenforceable and s.2 prohibits commercial surrogacy. This paper argues that one of the consequences of these principles has been an absence of consideration of the underlying ‘surrogacy contract’ in judicial decisions concerning ‘parental orders’: the post birth order that transfers legal parenthood from the surrogate to the intended parent, set out in s.54 of the Human Fertilisation and Embryology Act 2008. Instead, other interests have been focused upon within judicial language, particularly the ‘best interests of the child’ and a related emphasis on reflecting the ‘status’ and ‘identity’ of the child(ren). Moreover, this language is reflected within the wider ‘reform’ agenda regarding the regulation of surrogacy. This conceptual approach obscures the contract between the parties which is at the heart of any surrogacy arrangement. Thus, this paper argues that this absence of contemporary consideration of the contractual nature of surrogacy arrangements reflects the disregarding of the sexual contract that Pateman identified 30 years ago.